2017
DOI: 10.3390/su9071284
|View full text |Cite
|
Sign up to set email alerts
|

Time-Spatial Convergence of Air Pollution and Regional Economic Growth in China

Abstract: Abstract:The haze pollution caused by fine particulate matter (PM 2.5) emissions has become one of the most crucial topics of sustainable environmental governance in China. Using the average concentration of PM 2.5 in China's key cities from 2000 to 2012, as measured by aerosol optical depth, this study tested the time-spatial convergence of fine particulate matter pollution in China. The results show that there is a trend of absolute convergence between timespan and China's PM 2.5 emissions. At the same time,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…A wide variety of studies conducted on the topic so far is mostly limited to testing the existence of EKC in the Asia region [3,19] or to limit the scope to find the monotonic effect of different variables on the pollution emissions in South and Southeast Asia [15][16][17][18] and does not proceed to incorporate spatial effects. Other than studies conducted on China [1,2,[5][6][7][8][21][22][23][24][25][26][27], no extensive research has been done on EKC with the prevalence of spatial effects in the panel of East Asia region which is a vast research gap that this study focuses on filling.…”
Section: Theoretical and Empirical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…A wide variety of studies conducted on the topic so far is mostly limited to testing the existence of EKC in the Asia region [3,19] or to limit the scope to find the monotonic effect of different variables on the pollution emissions in South and Southeast Asia [15][16][17][18] and does not proceed to incorporate spatial effects. Other than studies conducted on China [1,2,[5][6][7][8][21][22][23][24][25][26][27], no extensive research has been done on EKC with the prevalence of spatial effects in the panel of East Asia region which is a vast research gap that this study focuses on filling.…”
Section: Theoretical and Empirical Frameworkmentioning
confidence: 99%
“…Using data from 2010-2012 from China, Pu [8] argued that there is a spatial difference between several parts of the country regarding the convergence between growth and emissions rate. While the study has landed on robust conclusions, it needs further evidence using panel data that can support this inference.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To prevent haze pollution, we should examine its main impact factors to define the relevant core control elements and on this basis propose the policy management program [14]. Many researchers have explored the factors contributing to pollutions, including both natural and socio-economic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Using the average concentration of PM 2.5 in China's major cities from 2000 to 2012, as measured by aerosol optical depth, Zhengning Pu tested the time spatial convergence of fine particulate matter pollution in China [15]. He showed that the growth rate of PM 2.5 in the middle and western zones is significantly higher than that of the eastern zone and the correlation test between regional economic growth and PM 2.5 emissions suggests a significant positive N-type Environmental Kuznets Curve (EKC) [15]. It implies a kind of balloon effect that the strong regulation on the eastern zone caused an exodus of the energy-intensive or heavy GHG-emitting industries into the western and central zones.…”
Section: Regulation Toward Green Technologymentioning
confidence: 99%